(untitled) (Journal of Geography and Environmental Management, 2025)
Glaciers are the most sensitive natural objects to climate change, so their volume and area change significantly under the influence of climatic factors. The melting of glaciers under the direct impact of global warming is one of the most acute environmental problems of our time. Mountain glaciers are the most dependent on climate change and their dynamics have a direct impact on ecosystems, life and economic activities of the population in the lower reaches of rivers. Intensive melting of glaciers in the research region may cause drinking water shortages and also increases the risk of hazardous processes such as mudflows, snow avalanches, rock-slides and floods. In this regard, the problem of deciphering, monitoring, assessing and mapping area changes of glaciers is very relevant. The main objective of the study is to automate and semi-automate the interpretation of mountain glacier boundaries and analyze their dynamics in the study area. This will be accomplished by using Landsat and Sentinel-2 satellite images taken at different time intervals. Landsat 7ETM+, Landsat 8 OLI, Sentinel-2 space images were used as initial data, using GIS-technologies and remote sensing methods, processing and classification of multispectral space images, expert correction of automated interpretation results and comparative analysis. As a result of the research, the contours of the Ile Alatau glaciers were determined using automated interpretation methods applied to Landsat and Sentinel-2 space images. Vector layers with attributive data were built using the ArcGIS program. The dynamics of glacier areas under conditions of climate change were analyzed. The results allow monitoring and assessment of water resources changes and natural hazards in the context of climate change. Satellite systems make it possible to get operational information to consumers about ice stockpiles in hard-to-reach mountain regions. Keywords: GIS technologies, Earth remote sensing, interpretation, glaciers, Sentinel 2, Landsat-8, satellite imagery, natural hazards